Pemberdayaan Karang Taruna Dusun Malasan melalui Produksi Pupuk Organik Cair Asari untuk Subsidi Pupuk kepada Kelompok Tani - Bandiyah Sri Aprillia; Yossi Safitri; Ayu Siti Aminah (WARTA LPM, 2021)
The Covid-19 pandemic has impacted the people of Malasan Hamlet, Ketitang Village, Juwiring District, Klaten Regency, Central Java. The impact experienced by youth in the area appeared in the form of layoffs by companies. The objective of Innovillage Program is to be a community service program aimed to explore and utilize the potential of Dusun Malasan to improve the standard of living of the village community through empowering youth organizations. The youth organization, which consists of young people in Dusun Malasan accompanied by Telkom University, are trained as peer mentors and disseminators. Youth organizations as peer mentors are responsible for the production and testing of their processed liquid organic fertilizers. Karang Taruna as a disseminator conducts training activities or production workshops and procedures for using liquid organic fertilizers to farmer groups. Karang Taruna also conduct commercialization training to farmer groups. The raw materials to be used are raw materials that are easily found in this area, namely, cow dung and banana trees. Based on the results of testing the POC concentration on the height of rice plants, it was shown that POC spraying with a concentration of 0.6% was able to increase plant height after 30 days of planting. Meanwhile, spraying 0.4% and 0.6% POC on 60-day-old plants showed only a slight difference in height. In addition, giving POC with a concentration of 0.2% was able to increase the number of tillers at the age of 30 and 60 days. After conducting training on the production and marketing of POC in Karang Taruna, Dusun Malasan, more than 85% of the members of the Youth Organizations were able to practice the POC production and marketing process.